Factors influencing public university students' career choice: Lesson learned from Bangladesh - Shila, Sharmin; Barman, Ram Proshad; Nishat, Arifuzzaman (Indonesian Journal of Social Sciences, 2025)
Most public university students in Bangladesh have career-related issues in the form of either career indecision or making the wrong choice. Hence, the study aims to identify the factors that influence public university students' job choices. The study employed a quantitative approach. Begum Rokeya University, Rangpur (BRUR) was selected purposively, then using simple random sampling to get 100 participants between January - July 2023. The study discovered that social and cultural elements, environmental factors, economic concerns, educational considerations, career aid and counseling, and personality qualities all had an impact on their career choices. However, economic factors, especially, motivate them to choose highly paid and status-oriented jobs. In addition, the students (94%) who were aware of career choice, possessed (60%) to work in the Bangladesh Civil Service (BCS) for respect, social safety, and financial stability. Moreover, only 40 percent of the students showed interest in working in other government jobs, non-government jobs, and a few of them identified business as their next workplace. In a nutshell, having a job in BCS is the priority of students, which reflects the notion of dependency on the government instead of being an entrepreneur and self-employed. However, the findings will be useful to scholars, students, job seekers, and the general public who are worried about career choices, both locally and abroad.